DESKRIPSI PEMAHAMAN KONSEPTUAL SISWA PADA KONSEP STRUKTUR ATOM DAN SISTEM PERIODIK UNSUR (SPU) - Kisdiono, Toyib Febri (Arfak Chem: Chemistry Education Journal, 2023)
Students' conceptual understanding of chemistry material is very important because good conceptual understanding can help to solve a problem, connect it with other relevant knowledge, and make it easier to study related material. This research aims to describe students' conceptual understanding of atomic structure and SPU material. This study employs a qualitative descriptive research method and approach. The research instrument is a multiple-choice test, with 25 questions divided into six indicators. We collected data through written tests. The data analysis process employs descriptive statistics, specifically using percentages. The research shows that students have a good understanding of all of the indicators. They understand that 42.59% of students in the sufficient category understand how electrons, protons, and neutrons relate to isotopes, isotones, and isobars. However, 33.70% of students in the poor category understand and can figure out the electron configuration. 19.16% of students in the very poor category can figure out the quantum number. 32.10% of students in the poor category can figure out periods and groups in SPU. And 32.10% of students in the less category have a good understanding of the periodicity of elements. The research results show that there is a need to improve the learning process, either through the application of learning models or the use of appropriate learning media, so that students' conceptual understanding can increase.